PREVALENCE OF ANEMIA AND ASSOCIATED FACTORS AMONG ADULTS UNDERGOING PERIODIC HEALTH EXAMINATIONS AT VINMEC SMART CITY INTERNATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the prevalence of anemia and analyze associated risk factors among adults undergoing periodic health examinations at Vinmec Smart City International General Hospital.Methods: A cross-sectional study was conducted on 2131 adults (aged ≥ 18 years). Anemia was diagnosed based on World Health Organization criteria. Data were analyzed using SPSS 20.0, with the Chi-square test employed to identify associations.Results: The overall prevalence of anemia was 8.7%. The condition was predominantly mild (93.5%), with no severe cases recorded. Normocytic normochromic anemia accounted for 50.8%, while microcytic hypochromic anemia accounted for 22.2%. The prevalence was significantly higher in females compared to males (14.6% vs. 1.4%; p < 0.001). Regarding age, the younger group (≤ 35 years) exhibited a higher rate of anemia than the older group (10% vs. 7.5%; p = 0.04). Notably, anemia prevalence was inversely correlated with BMI, being highest in underweight individuals (11.8%) and lowest in the overweight, obese group (6.1%) (p < 0.001).Conclusion: While the prevalence of anemia in this screening population is lower than that of the general population, it remains a significant health concern for young females and underweight individuals.
Keywords: Anemia, periodic health examination, adults, Vinmec.